Perceptions of ASEAN Youth Towards Japan: Impact on the Japanese Economy - Muhammad Riduan Bin Samad (Center for Southeast Asian Social Studies (CESASS), 2020)
In exerting soft power to pursue its economic interests in Southeast Asia, Japan has been challenged by its regional rivals. In retaining its position, Japan needs to win the hearts and minds of ASEAN youths, a generation moving toward the middle class with significant purchasing power. Hence, a three-month online survey and a series of focus group discussions were conducted to gather information and perspectives about Japan from 222 youth respondents from the ten ASEAN countries. It was found that ASEAN young generations have a good impression of Japan and Japanese people, even though most of them have never been to Japan or personally interacted with a Japanese person. This perception has been built most effectively by Japanese popular culture, including animation and manga. However, youth development and exchange programs, and interactions with Japanese people are less influential factors, especially for those who are from lower socioeconomic backgrounds. Thus, exposures to Japanese products and services to ASEAN young generations have not only contributed to the Japanese economy but also contributed to the positive perception toward the country. Given tighter government budgets, streamlining Japan’s soft power strategy will help it win over ASEAN youths for its future economic prosperity.